Self-doping of Nb2O5NC by cathodic polarization for enhanced conductivity properties and photoelectrocatalytic performance - Khan, Saad Ullah [UNESP]; Hussain, Sajjad; Perini, João Angelo Lima [UNESP]; Khan, Hammad; Khan, Sabir [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier, 2021)
A simple novel electrochemical reduction approach was developed for the self-doping of Nb4+ in niobium oxide nanochannels (Nb2O5NC), changing the conductivity, optical properties, and photocatalytic properties of the material. Nb2O5NC was synthesized using different electrolytes: 0.4 wt% HF in 1 M H2SO4 (EI), 0.4 M NH4F in glycerol (EII), and 0.25 g NH4F with 4 vol% water in glycol at 50 °C (EIII). Field emission scanning electron microscopy (FEG-SEM) analysis showed well-organized arrays of Nb2O5 nanochannels produced on Nb foil, with varying tube diameters in the order EII < EI < EIII and film thickness in the order EI < EII < EIII, which drastically affected the photocurrent vs. potential curves. In order to self-dope the Nb2O5, the samples were electrochemically reduced in 0.1 M KH2PO4 buffer solution (pH 10) for 5 min, at −2.5 V vs. Ag/AgCl, resulting in the doped samples denoted P-EI, P-EII, and P-EIII. The results showed that reduction of Nb5+ to Nb4+ occurred for all the Nb2O5NC samples, leading to decreased surface charge transfer resistance between the Nb2O5NC and the electrolyte, as well as increases of the charge carrier density and photocurrent for all the self-doped samples, compared to undoped samples. Sample P-EI was also tested for the degradation of reactive red 120 (RR120) dye, achieving efficient photoelectrocatalytic degradation of a 10 mg L−1 dye solution. These results reveal that the self-doping approach can enhance the photoelectrocatalytic properties of Nb2O5 photoanode, offering an alternative way for the removal of reactive dyes.
Keywords: Electrochemical reduction; Photoelectrocatalysis; RR120 dye; Synthesis of Nb2O5NC